Monoclonal antibodies targeting the synthetic peptide corresponding to the polybasic cleavage site on H5N1 influenza hemagglutinin - Tsai Henry J; Chi Li-Ann; Yu Alice L (Journal of Biomedical Science, 2012)
Abstract Background Avian influenza H5N1 virus is highly pathogenic partially because its H5 hemagglutinin contains a polybasic cleavage site that can be processed by proteases in multiple organs. Methods Monoclonal antibodies (mAb) specific to the synthetic peptide of hemagglutinin polybasic cleavage site of H5N1 virus were raised and tested for their neutralizing potential. Results Purified mAb showed suppression of H5N1 pseudovirus infection on Madin-Darby Canine Kidney (MDCK) cells but the efficacy was less than 50%. Since those mAb are specific to the intact uncut polybasic cleavage site of hemagglutinin, their efficacy depends on the extent of hemagglutinin cleavage on the viral surface. Conclusions Proteolytic analysis suggests the low efficacy associated with those mAb may be due to proteolytic cleavage already present on the majority of hemagglutinin prior to the infection of virus.